Mối quan hệ giữa chất lượng tín hiệu và sự tin tưởng vào rau an toàn: Vai trò trung gian của sự tin tưởng vào nhà bán lẻ tại Thành phố Hồ Chí Minh - Bui Thanh , Trang; Dinh Vu , Dinh; Phan Thi , Ly; Nguyen Anh, Duc (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2021)
This study investigates the relationship between signal quality and consumer trust and is conducted by a combination of qualitative and quantitative methods. Based on the survey results of 502 customers who have been buying safe vegetables at supermarkets and convenience stores dealing in food in Ho Chi Minh City, the results show: (1) The positive influence of retailer’s signal quality (including clarity, credibility, and consistency) on customer trust in the retailers and trust in the safety of safe vegetables; (2) the positive relationship between trust in the retailers and trust in the safety of safe vegetables; and (3) the mediating role of trust in the retailers. The research results contribute to theoretical gaps in the relationship between the conceptual frameworks. At the same time, this research contributes to adjusting and supplementing the scale of concepts that can serve as a basis for future studies.
Keywords: Signal quality; Trust; Food safety; Safe vegetables; Retailers